Pola Komunikasi Daiyah dalam Pembinaan Keagamaan di Muslimah Wahdah Islamiyah Daerah Makassar - Sari, Hijrayanti (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
The aim of this research is to identify the communicational pattern applied by Muslimah of Wahdah Islamiyah in the effort of religious coaching. This research applies qualitative and descriptive method. Method of collecting respondents are purposive sampling where the samples are 10 female preachers of Islamic study groups. The data are acquired from interview, observation and documentation. The result shows that religious coaching conducted by the female preachers of Wahdah Islamiyah is in the context of small group communication with informative and persuasive technique. Communicational pattern used is the wheel pattern and star pattern.